Audit Fee Differential, Audit Effort, and Litigation Risk: An Examination of ADR Firms - Bronson, Scott N.; Ghosh, Aloke (Al); Hogan, Chris E. (Contemporary Accounting Research, 2017)
Abstract Prior studies find that audit fees are higher for cross‐listed firms, and these studies primarily attribute the incremental fees to added litigation costs. In this study, we investigate whether the higher audit fees that foreign firms cross‐listed in the United States pay are also attributable to incremental audit effort associated with U.S. disclosure requirements and a more stringent U.S. auditing environment. By comparing audit fees of foreign cross‐listed firms to U.S. domiciled firms and to non‐cross‐listed foreign firms, we are able to decompose incremental audit fees into portions attributable to added audit effort and to added litigation costs. We find that, on average, foreign firms cross‐listed in the United States pay significantly higher fees than domestic U.S. firms and foreign firms that do not cross‐list. Furthermore, we find that audit effort is almost as important as litigation costs in explaining the higher fees associated with foreign cross‐listed firms; our estimates suggest that between 29 percent and 48 percent of the incremental fees are attributable to incremental audit effort. In addition, the total cross‐listing premium is increasing in the difference between the U.S. auditing regulatory environment and that of the home country of the cross‐listed firm. Our study improves our understanding of the role of audit effort in explaining the added fees charged by auditors when foreign firms cross‐list in the United States.